1979
DOI: 10.2134/jeq1979.00472425000800020002x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Water Movement in Macropores

Abstract: Current views of infiltration of water into soils are based on nearly complete displacement of soil water by incoming water. In general, rapid flow down macropores and its effect on water and solute distribution have not been considered very important by the majority of researchers. We present evidence to show that flow of water through macropores is important in soil and ground water recharge and in salt movement through soils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
145
0
3

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(157 citation statements)
references
References 0 publications
6
145
0
3
Order By: Relevance
“…In this experiment, a 3 X 5 cm area was available on each slide. The thin sections were placed, glass side down, on a Hewlett Packard Scan Jet 5100c flatbed scanner and scanned in black and white at 60 pixels per cm 2 . At this resolution, identification of pores with diameters > 160 |xm is possible.…”
Section: Macropore Characterization Using Photoshopmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, a 3 X 5 cm area was available on each slide. The thin sections were placed, glass side down, on a Hewlett Packard Scan Jet 5100c flatbed scanner and scanned in black and white at 60 pixels per cm 2 . At this resolution, identification of pores with diameters > 160 |xm is possible.…”
Section: Macropore Characterization Using Photoshopmentioning
confidence: 99%
“…Extensive groundwater monitoring and experimental data have revealed that preferential flow through macropores and fractures may be a primary mechanism for rapid leaching of agricultural chemicals and other potential pollutants into surface water and groundwater (1,2). Bouma and Wosten (3) found that the shape of breakthrough curves and saturated and unsaturated hydraulic conductivity are greatly influenced from a few macropores that represent a small percentage of the total volume in undisturbed soil samples.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, a manutenção da estabilidade da estrutura, decorrente da ausência de preparo e presença da palha na superfície do solo, pode incrementar a infiltração de água (Thomas & Phillips, 1979;Dick, 1983;Crawford, 1994) e favorecer a lixiviação de herbicidas. O ambiente edáfico originado normalmente incrementa a diversidade, a atividade e a biomassa microbiana, acentuando a degradação e/ou transformação biológica de herbicidas aplicados nesses solos (Walker et al, 1992;Mueller et al, 1999).…”
Section: Resultsunclassified
“…Although bulk density often tends to be higher under no-till, and there is frequently more air-filled porosity in plowed relative to no-till soils, Gantzer and Blake (1978) observed more macropores (soil pores larger than 1 mm) in no-till soils relative to plowed soils. The importance of macropores in water infiltration has been shown by Thomas and Phillips (1979). experiment indicated that mulches tended to reduce soil compaction below 1 foot ( fig.…”
Section: Soil Water Storagementioning
confidence: 89%